Pertanggungjawaban Pidana Terhadap Pelaku Penyalahgunaan Narkotika yang Dilakukan Narapidana di Lembaga Pemasyarakatan Way Huwi Provinsi Lampung - Zainudin Hasan (PRANATA HUKUM, 2018)
In the current era of Narcotic trafficking involves not only the society, but also the network of citizens in the status of convicted criminal in the Correctional Institution. The problems of this research are: a. causing factors of Narcotics abuse that conducted by convicted criminal, b. How is criminal responsibility to the Narcotic abusers that conducted by convicted criminal, c. How efforts to overcome Narcotics abuse that conducted by convicted criminal in the Narcotic Correctional Institution Class II A Bandar Lampung. The results of this research indicate that (1) Causing factors of Narcotics abuse that conducted by convicted criminal in the Narcotic Correctional Institution Class II A Bandar Lampung namely there is an intrinsic and extrinsic factor, and then the existence of market of Narcotics traffiking in the Correctional Institution. (2) Criminal responsibility to the Narcotic abusers conducted by convicted criminal in the Narcotic Correctional Institution Class II A Bandar Lampung which is based on errors that meet the element against the law and there is no reason for the elimination of the unlawful nature of the deed. The criminal responsibility is that the defendant can be convicted, then the Panel of Judges sentence to the defendant who is still have a status of convicted criminal. (3) Efforts to overcome Narcotics abuse conducted by convicted criminal in the Narcotic Correctional Institution Class II A Bandar Lampung by using non-penal (counseling, social education, resocialization, on convicted criminal with have Narcotics track record) and penal ways are done by legal effort based on provisions of legislation.